Treatment of «unhappy triad of the elbow» and its consequences - Kurinnyi, Igor; Strafun, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Despite on the development of treatments for intra-articular damages the recovery of function after severe injuries of the elbow is complicated problem and is far from a solution. Objective: To develop a differentiated tactics of treatment for patients with the «unhappy triad of the elbow» depending on timing of the damage, its character and associated injuries. Methods: Outcomes in 27 patients (14 men, 13 women aged 17 to 66 years) with the «unhappy triad of the elbow» were analyzed. In 11 cases (41 %) there was damage to the right upper extremity, in16 patients (59 %) the left elbow was injured. The period of follow-up ranged from 3 to 120 months. Long-term results of treatment were evaluated in 22 patients out of 27 ones according to a scale of Mayo Elbow Performance Score (MEPS). Results of treatment in patients with «unhappy triad» depend on the severity and character of the injuries and character of previous surgery. According to MEPS in operated patients with «unhappy triad of the elbow» there were achieved excellent results in 5 cases (23 %), good — in 10 (45 %), satisfactory – in 5 (23 %), and poor — in 2 (9 % ) ones. Conclusion: «unhappy triad» is a serious injury of the elbow which requires the full restoration of all damaged structures with a dosed postoperative rehabilitation in early terms after injury. Saving the radial head and the coronoid process of the ulna are pledge of restoration of full function of the elbow joint. With the combination of «unhappy triad of the elbow» with the Essex-Lopresti injury except for reconstructive surgery on the elbow it is necessary to carry out corrective surgeries in order to eliminate radiation talipomanus and conflicts developing in the distal radioulnar articulation.